Effects of Thailand and Sri Lanka agronomic practices on mungbean (Vigna radiata (L.) Wilczek) production in rice-based cropping system - Peiris, Hiran; Kaveeta, Rungsarid; Rangsipaht, Savitree; Pitakdantham, Roongroj (Agriculture and Natural Resources, 2016)
The effects of agronomic practices were evaluated on mungbean production, using a randomized complete block design conducted at the Farming Research Development Center, Phaniat sub-district, Khok Sumrong district, Lop Buri province, Thailand during February to July 2015. Five agronomic practices (each with four replications) were testeddThai farmer practice (TFP) as the control; Thailand recommendation (TR); Sri Lankan farmer practice (SLFP); Sri Lankan new recommendation (SLNR); and Thailand recommendation with paddy straw mulch (TRM)deach practice was composed of different tillage methods, seeding rates, mulching and seed inoculation (with Rhizobium). At the maturity stage, the lowest height (38.04 cm) was found in TFP compared to 78.8%, 56.6%, 31.5% and 20.8% height increases reported in TRM, SLNR, SLFP, and TR, respectively. Furthermore, TFP had the lowest leaves per plant at maturity (8.73), whereas the percentage of leaves per plant at maturity in TR, SLFP, SLNR and TRM was 20.9%, 27.4%, 33.1% and 60.1%, respectively, higher than in TFP. TFP produced the lowest yield (0.657 t/ha) while TRM, TR, SLFP and SLNR which produced increased yields by 109.13%, 41.4%, 46.1% and 86.8%, respectively, compared to the control. Overall, the results showed that the method of tillage, mulching and inoculum collectively determined the growth and seed yield of mungbean in a ricemungbean cropping system.